ChemInform Abstract: Iodoarene‐Catalyzed Stereospecific Intramolecular sp3 C—H Amination: Reaction Development and Mechanistic Insights. Issue 47 (November 2015) - Zhu, Chendan; Liang, Yong; Hong, Xin; Sun, Heqing; Sun, Wei‐Yin; Houk, K. N.; Shi, Zhuangzhi
Abstract: A new method for preparation of γ‐lactams through iodoarene‐catalyzed intramolecular amination is developed.